Sistem Pendukung Keputusan Pemilihan Line-up Pemain Sepak Bola Menggunakan Metode Fuzzy Multiple Attribute Decision Making dan K-Means Clustering - Aldi Nurzahputra; Afrizal Rizqi Pranata; Aji Puwinarko (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2017)
In football, the selection of players line-up is based on their statistical performance. In this research, the line-up selection can implement the decision support system (DSS) with FMADM SAW method. The criteria were used are goal, assists, saves, clean sheets, yellow cards, red cards, games, and an own goal. Then, the assessment players performance is using K-Means Clustering. There are two clusters: cluster_cukup and cluster_baik. The system used Manchester City player data in Forward, Midfielder, Defender and Goal Keeper position. The purpose of this research is applying the FMADM and K-Means Clustering method to the system. Based on the results, the line-up selection can be processed by FMADM method and the performance assessed by K-Means Clustering method. By using the system, the selection and the assessment can be conducted and give the best decision for football coach objectively.